DEVELOPMENT OF E-MODULES BASED ON LOCAL WISDOM MATERIALS OF MOMENTUM AND IMPULSES OF CLASS X SMA (Physics and Science Education Journal (PSEJ), 2022)
This study aims to develop an e-module based on local wisdom for the momentum and impulses of Class X SMA. This research was a research and development that uses a 4-D development model consisting of 4 stages, namely Define, Design, Develop, and Disseminate. The subjects of this study were 2 material experts and media experts, as well as class X students at SMA Negeri 2 Jambi City, totaling 35 students. There were 2 types of data obtained, namely qualitative data and quantitative data. The instruments used in this study were observation sheets, interview sheets, material and media expert validation sheets and student perception questionnaires. Qualitative data were analyzed descriptively and quantitative data were analyzed using descriptive statistics. This research produces e-modules based on local wisdom material on momentum and impulse. Jambi's local wisdom is used as a context to explore the concepts of momentum and impulse. The results of material validation obtained a percentage of 95.63% in the "Very Good" category and media experts at 94.90% in the "Very Good" category. The results of students' perceptions of e-modules based on local wisdom on momentum and impulse materials obtained a score of 89.66% in the "Very Good" category.